The Impact of Capital, Labor, Education, and E-commerce on the Income of Culinary MSME - Wulandari , Alysa Dwi; Arianti, Fitrie (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2025)
This study investigates the effects of capital, labor, education, and e-commerce on the income of micro, small, and medium-sized enterprises (MSMEs) in the culinary sector of Semarang City, Indonesia. Utilizing a quantitative approach, primary data were gathered through surveys of culinary MSME owners using structured questionnaires. Multiple linear regression analysis was employed to examine the individual and joint influence of the selected variables on income. The findings reveal that capital, labor, education, and e-commerce each have a significant and positive effect on MSME income. Collectively, these variables account for 71.3% of the variation in income, highlighting their critical role in enhancing business performance. The study underscores the importance of optimizing internal business factors to boost productivity, competitiveness, and earnings within the culinary MSME sector. Keywords: MSME income, capital, labor, education, e-commerce, culinary business.